2019
DOI: 10.1145/3360498
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Interdependent Privacy

Abstract: The privacy of individuals does not only depend on their own actions and data but may also be affected by the privacy decisions and by the data shared by other individuals. This interdependence is an essential aspect of privacy and ignoring it can lead to serious privacy violations. In this survey, we summarize and analyze research on interdependent privacy risks and on the associated (cooperative and non-cooperative) solutions. We also demonstrate that interdependent privacy has been studied in isolation in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 151 publications
0
36
0
Order By: Relevance
“…Besides, the phenomenon violates individuals' right to privacy and threatens the ideal of privacy self-management itself, independently from whether it produces concrete (latent, tangible or intangible) harm or not, and inde-10. This was also demonstrated by Humbert et al (2020) regarding interdependent privacy. However, through my analysis of privacy externalities, yet more of these clusters have been uncovered-accentuating the point that "research on the topic has been conducted in isolation in different communities" (ibid, pp.…”
Section: Privacy Externalitiesmentioning
confidence: 56%
See 1 more Smart Citation
“…Besides, the phenomenon violates individuals' right to privacy and threatens the ideal of privacy self-management itself, independently from whether it produces concrete (latent, tangible or intangible) harm or not, and inde-10. This was also demonstrated by Humbert et al (2020) regarding interdependent privacy. However, through my analysis of privacy externalities, yet more of these clusters have been uncovered-accentuating the point that "research on the topic has been conducted in isolation in different communities" (ibid, pp.…”
Section: Privacy Externalitiesmentioning
confidence: 56%
“…Part of the contribution made by this article is the collection of relevant literature, which otherwise stands in isolated clusters and refers to a similar phenomenon using different concepts, such as: joint controllership, and privacy infringements (Helberger and van Hoboken, 2010;van Alsenoy, 2015;Edwards et al, 2019) or infringements of data protection law and networked services (Mahieu et al, 2019); collective privacy (Squicciarini et al, 2009) and collective action problems in privacy law (Strahilevitz, 2010); multi-party privacy (Thomas et al, 2010); collateral damage and spillover (Hull et al, 2011;Symeonidis et al, 2016); interpersonal management of disclosure (Lampinen et al, 2011); networked privacy (boyd, 2011;Lampinen, 2015;Marwick and boyd, 2014); interdependent privacy (Biczók and Chia, 2013;Symeonidis et al, 2016;Pu and Grossklags, 2017;Kamleitner and Mitchell, 2019); peer privacy (Chen et al, 2015;Ozdemir et al, 2017); multiple subjects personal data (Gnesi et al, 2014); privacy leak factor, shadow profiles and online privacy as a collective phenomenon (Sarigol et al, 2014); privacy externalities (Laudon, 1996, pp. 14-6;MacCarthy, 2011;Humbert et al, 2015Humbert et al, , 2020Symeonidis et al, 2016;Choi et al, 2019), especially as compared to externalities in the context of environmental pollution (Hirsch, 2006(Hirsch, , 2014Hirsch and King, 2016;Froomkin, 2015;Nehf, 2003;Ben-Shahar, 2019); 1 genetic groups…”
Section: Introductionmentioning
confidence: 99%
“…Humpert et al [26] survey the interdependent privacy problems and technical solutions in various domains. They have found that almost all the technical solutions focus on either photos or generic data (including photos).…”
Section: Connection To Other Directions In Privacymentioning
confidence: 99%
“…In short, what is at stake is not simply the privacy of individuals, but the social and moral ordering of the group [9]. In this respect, we find that existing approaches to collaborative data management furnished by efforts to engineer 'interdependent privacy' [34] do not resonate with the ways in which access control is socially managed and negotiated within the home. We conclude with a discussion of the implications of these findings.…”
Section: Introductionmentioning
confidence: 97%